2008
DOI: 10.1162/asep.2008.7.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Financial Liberalization, Crises, and Economic Growth

Abstract: The paper computes the effect of financial liberalization on economic growth by combining the results of a panel model with those of a probit model. It finds a positive net effect from financial liberalization to growth. Surprisingly, we find that the net effect on growth is larger in the crisis-experienced country group than in the overall sample group. Our guess is that the crisis-experienced countries are mostly developing countries that usually enjoy higher growth rates than the developed countries because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The coefficient of financial repression in the Probit equations for a debt crisis is significant and negative, suggesting that financial repression (as measured by the FRI index) could reduce the risk of a crisis. This result can be compared with the findings of Lee and Shin (2008) and Rancière, Tornell, and Westermann (2006), who found that financial repression reduces the risk of a financial crisis. A change in the FRI value in the previous three years (full liberalization, or the introduction of controls) also appears with a significant coefficient of the same sign, but of lower magnitude and at a lower confidence level, while a more general change in the interest control regime does not exhibit a significant coefficient.…”
Section: Impact Of Financial Repression On Debt Crisesmentioning
confidence: 61%
See 3 more Smart Citations
“…The coefficient of financial repression in the Probit equations for a debt crisis is significant and negative, suggesting that financial repression (as measured by the FRI index) could reduce the risk of a crisis. This result can be compared with the findings of Lee and Shin (2008) and Rancière, Tornell, and Westermann (2006), who found that financial repression reduces the risk of a financial crisis. A change in the FRI value in the previous three years (full liberalization, or the introduction of controls) also appears with a significant coefficient of the same sign, but of lower magnitude and at a lower confidence level, while a more general change in the interest control regime does not exhibit a significant coefficient.…”
Section: Impact Of Financial Repression On Debt Crisesmentioning
confidence: 61%
“…13 Among others, Achy (2003); Bekaert, Harvey, and Lundblad (2005); Ben Gamra (2009); Bussière and Fratzscher, (2008); Bonfiglioli and Mendicino (2004); Garita (2009); Lee and Shin (2008); McLean and Shreshta (2002); Rancière, Tornell, and Westermann (2006); Romero-Àvila (2009); and Tornell, Westermann, and Martinez (2004). See the metastudy compiled by Bumann, Hermes, and Lensink (2013).…”
Section: Panel Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Lee and Shin (2008) dissected the effects of financial liberalisation into direct and indirect effects. The direct effects are clearly the benefits that arise in terms of the removal of frictions in the markets, thus leading to lower borrowing costs.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%